The role of amygdala and hypothalamus in GABA(A) antagonist bicuculline-induced cardiovascular responses in conscious rats - ONAT, FİLİZ; GÖREN, MEHMET ZAFER (ELSEVIER SCIENCE BV, 1996)
gamma-Aminobutyric acid (GABA) is known to play an important role in the central control of cardiovascular functions. GABAergic agonists and antagonists elicit blood pressure and heart rate changes when injected into the brain. It was demonstrated here that bicuculline methiodide (BMI), a GABA(A) antagonist caused dose-dependent increases in both blood pressure and heart rate in conscious rats when injected intracerebroventricularly. The roles of the central nucleus of the amygdala (CeA), the paraventricular nucleus (PVN) and the dorsomedial nucleus (DMH) of the hypothalamus in BMI-induced blood pressure and heart rate changes were investigated in this study. The pressor effect of BMI was significantly attenuated by the electrolytic ablation of DMW and PVN, whereas it was only slightly, but insignificantly reduced by CeA lesions. The microinjection of BMI into the DMH and the PVN elicited significant presser and tachycardic responses whereas only a slight increase was observed in rats injected BMI into the CeA. The BMI-induced increases in both blood pressure and heart rate were more prominent when given into the DMH. These results indicate that the DMH plays an important role in GABAergic control of cardiovascular functions. The PVN and CeA seem to have a minor part in this respect.
Keywords: gamma-aminobutyric acid; amygdala; hypothalamus; blood pressure; heart rate; rat; SPONTANEOUSLY HYPERTENSIVE RAT; POSTERIOR HYPOTHALAMUS; PARAVENTRICULAR NUCLEUS; SYMPATHETIC OUTFLOW; ANESTHETIZED RATS; HEART-RATE; MICROINJECTION; STIMULATION; ACTIVATION; INJECTION